Rancangan Perbaikan Dokumen dan Pengendalian Hazard Analysis Critical Control Point Produk Olahan Fillet di PT “X” - Joshua Revindy Chandra; I Nyoman Sutapa; Nova Sepadyati (Jurnal Titra, 2019)
This article discusses the design improvements documents and control of hazard analysis critical control point in a seafood processing company. This system ensures the quality by analyzing hazards on each process as well as to determine the appropriate responses to the process. Problems occurred is not ready to conduct the HACCP system, as in the determination of the potential dangers of the company causes opportunities do not judge objectively so that the risk is not accurate. Another problem that arises is the method of handling the prerequisite was implemented by the company in the form of Good Manufacturing Procedures (GMP) and Sanitation Standard Operating Procedures (SSOP) is irrelevant and incomplete. The results of this research are the odds cause potential dangers that are already associated with an existing data so that more accurate risk control priorities. Also, the research methods produce GMP and SSOP prerequisite programs are more complete and ready to be run by the company.